DETERMINANT OF DENTAL CARIES AT AN EARLY AGE IN TK KHALIFAH 2 JAMBI CITY - Pahrur Razi; Surayah Surayah (Poltekkes Kemenkes Jambi, 2020)
Background: Dental caries are a major problem of dental and oral health and that have the potential for lifelong disorders. Therefore, dental and oral health can not be ignored especially in early childhood, because dental and oral health contributes to the perfect growth of children. However, the highest prevalence of caries was in the 5-9 year old age group at 92.6%. The purpose of the study was to determine the determinant of dental caries in early childhood in TK Khalifah 2 Jambi Year 2019. Method: This research is descriptive in analytics with a cross-sectional approach. The population in this study was all children of Kindergarten (TK) Khalifah 2 Jambi City. The number of 30 people, with sampling techniques using total sampling. Hypothesis testing in this study uses statistical test analysis that is chi-square test. Result: Dental caries is associated with cariogenic food eating habits (p-value 0.001) and dental health measures (p-value 0.017) and is not related to knowledge of dental health (p-value 0.618), and attitudes towards dental health (p-value 0.145). Conclusion: Cariogenic eating habits and brushing behavior are factors that have a relationship with dental caries, where respondents with low brushing behaviors had dental caries 2.6 times compared to respondents with good brushing behavior.